2020
DOI: 10.1002/jor.24945
|View full text |Cite
|
Sign up to set email alerts
|

Pelvis weight‐bearing ability after minimally invasive stabilizations for periacetabular lesion

Abstract: Periacetabular metastatic lesions cause debilitating weight-bearing pain and pose a risk of pelvic pathologic fracture. Minimally invasive percutaneous stabilization is an alternative palliative therapy over extensive open reconstructive surgeries. This study aimed to investigate the biomechanical behaviors of three distinct techniques of percutaneous periacetabular stabilization. A total of 20 composite hemipelves custom-made to contain Harrington type III periacetabular lesion based on a patient's computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When undergoing interventional procedures of the pelvic bone, one must be aware of the biomechanical properties of this complex osseous structure. It is of great importance to identify situations where cementoplasty alone can be sufficient from situations where additional osteosynthesis must be associated to provide the best needed stability [20]. Biomechanical studies of the pelvic bone have shown that the sacral promontory and the peri-acetabular region are the most constrained portions of the pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…When undergoing interventional procedures of the pelvic bone, one must be aware of the biomechanical properties of this complex osseous structure. It is of great importance to identify situations where cementoplasty alone can be sufficient from situations where additional osteosynthesis must be associated to provide the best needed stability [20]. Biomechanical studies of the pelvic bone have shown that the sacral promontory and the peri-acetabular region are the most constrained portions of the pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have compared various means of fixation, including cement-only fixation, screw-only fixation, and screw fixation with the addition of bone cement 10,11 . The construct stiffness and yield to failure were highest with the cement-and-screw combination group, followed by the cement-only fixation group and then the screw-only fixation group.…”
Section: Minimally Invasive Reinforcement Techniquesmentioning
confidence: 99%
“…In general, implants are positioned to bridge osteolytic defects and pathologic fractures while originating and terminating in stable bone. When screw fixation is employed, percutaneously injected cement can be performed through the cannulated screws to reinforce the screw landing site, enhancing the strength of the overall construct 28,29 …”
Section: Surgical Techniquementioning
confidence: 99%
“…25,27 Fixation constructs combining screws and cement have been shown to be more stable than those comprised of cement or screws alone. 28,29 A patient series using photodynamic balloons for fixation has shown functional improvement from surgical intervention; however, this fixation modality has yet to be compared to screws and cement. 14…”
Section: Fixation Constructsmentioning
confidence: 99%
See 1 more Smart Citation